The Nose-Bleed Syndrome: A Study on the Attitude of the College Students towards English Language Learning and Their Linguistic Self-Confidence in a Multi-Cultural Context - Annie Mae Berowa (Philippine Association of Institutions for Research, Inc., 2016)
The expression "nose-bleed!" has become the most popular expression among Filipinos when asked to speak in English. In the Philippines, English is the most feared language. This fear is seen in classes where students feel so anxious that they may mispronounce a word or that they may commit grammatical inaccuracies. This also happens during job interviews when most of the applicants would sweat out while using English. The study was undertaken to determine the profile of the select students as respondents of the study, their attitude towards English language learning, and the situation/s that they feel linguistically confident in using the target language in a multi-cultural context. The study was conducted at the Mindanao State University (MSU), Main Campus, in the Islamic City of Marawi. The study utilized both quantitative and qualitative data collection and analysis procedures. Survey questionnaire and Focus Group Discussion (FGD) were employed. The questionnaire was administered to 129 randomly selected Job Enabling English Proficiency (JEEP) Program students, and then the FGD was conducted to probe further certain points that require illumination. It was concluded that the respondents have a positive attitude toward learning the English language. It was also disclosed that the linguistic self-confidence of the respondents leaned more on the situation-specific self-confidence.